Protection of molybdenum containers used at uranium dioxide sintering from grain boundary diffusion of oxygen and nitrogen; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 3 - Makarov F. V. (Chemistry, 2007)
Заглавие с титульного листа